(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: There is no unanimously adopted approach to titrating laser parameters in subthreshold retinal laser photocoagulation without ophthalmoscopically visible fundus changes. Purpose: To investigate the ultrastructural changes in the rabbit chorioretinal complex following 577-nm conventional, selective or micropulse retinal laser photocoagulation (RLPC). Materials and Methods: Four rabbits (8 eyes) were involved in the experimental study and underwent the RLPC modes with the 577-nm system (Supra 577). Rabbits (n = 2/time point) were euthanized at postlaser days 1 and 14. Ultra-thin sections of their ocular tissue specimens were subjected to electron microscopy. In addition, 2 intact rabbits (4 eyes) were used as controls for comparison. Results: Conventional RLPC resulted in damage to RPE cells, all photoreceptor compartments and choriocapillaries; selective RLPC resulted in damage to RPE cells and photoreceptor outer and inner segments; and micropulse RLPC with the power setting adjusted to 50% threshold resulted in damage mostly to apical aspects of RPE cells and photoreceptor outer segments. Conclusion: 577-nm micropulse RLPC with the power setting adjusted to 50% threshold is a more photoreceptor- and choriocapillaris-sparing approach compared to conventional and selective RLPC, and can be used in clinical practice as a laser treatment approach with the least invasive effect on the chorioretinal complex.